Studi Kasus Pengaruh Kombinasi Pemberian Jus Buah Naga dan Senam Anemia (BuNga SaNemi) pada Remaja Putri dengan Anemia - Novi Vebianti; Endang Triyanto; Lita Heni Kusumawardani (UIMA Press, 2023)
Background: Teenager girls who have experienced menstruation are at high risk of suffering from anemia. Anemia is a level of hemoglobin or the number of red blood cells that is less than normal. One strategy that can be done to overcome the problem of anemia is by giving dragon fruit juice therapy and anemia exercises. This study aims to increase hemoglobin levels in teenage girls with anemia. Objectives: This study aims to evaluate the effect of dragon fruit juice and anemia exercises (BuNga SaNemi) in teenage girls with anemia. Methods: This research used a quantitative approach with the case study method. The research design was a quasi-experimental pretest-posttest without a control group design. Respondents were 2 teenager girls. The intervention was given for 7 days, namely 3 times exercise with a duration of 4-5 minutes and dragon fruit juice every day. Data analysis used the Wilcoxon test. Results: Provision of dragon fruit juice and anemia exercise (BuNga SaNemi) was proven to increase hemoglobin with an average increase of 7.5gr/dl. The results of the Wilcoxon test analysis are Sig. (2-tailed) of 0.001 <0.05 which indicates a significant difference in the hemoglobin value of the two clients before and after the intervention. Conclusion: Giving dragon fruit juice and anemia exercise (BuNga SaNemi) can be used as an alternative method to increase hemoglobin in teenager girls with anemia.